(untitled) (TAMADDUN NURI JURNALI, 2024)
this article analyzes the manipulative character of myths. Through the comparative analysis of the common and different aspects of the myths that appear in traditional and modern thinking, their epistemological and psychological aspects of occupying the minds of people are revealed. in addition, attention is paid to the study of concepts in this regard, which arose during the development of philosophical thinking. Also, the mechanisms of myth creation and popularization in modern societies are considered from a philosophical point of view. Based on the analysis of myths in a Eurocentric spirit, the possibilities of myths to manipulate the human heart and mind are revealed.